PENERAPAN AKUNTANSI LINGKUNGAN DALAM HAL PENGELOLAAN LIMBAH PRODUKSI PADA PERUSAHAAN PENGALENGAN IKAN TUNA PT. SAMUDRA MANDIRI SENTOSA BITUNG - Anis, Valencia Matthew; Sabijono, Harijanto; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The purpose of this study is to investigate how the application of environmental accounting in terms of managing production waste in fish canning companies PT. Samudra Mandiri Sentosa Bitung. This study is qualitative research. This study uses primary data. Primary data were collected by interview. The results of this study are PT. Samudra Mandiri Sentosa has identified, recognize, and measured environmental costs but the company has not made explicit and separate disclosure of environmental cost reports. Stages of treatment of environmental costs are treated as components of production costs, namely direct material costs, direct wage costs, and overhead costs.